Cellular Solids: Three‐Dimensional Printing of Elastomeric, Cellular Architectures with Negative Stiffness (Adv. Funct. Mater. 31/2014). (August 2014) - Duoss, Eric B.; Weisgraber, Todd H.; Hearon, Keith; Zhu, Cheng; Small, Ward; Metz, Thomas R.; Vericella, John J.; Barth, Holly D.; Kuntz, Joshua D.; Maxwell, Robert S.; Spadaccini, Christopher M.; Wilson, Thomas S.
<x xml:space="preserve">Abstract</x> Three‐dimensional printing of viscoelastic inks is demonstrated by E. B. Duoss, C. M. Spadaccini, T. S. Wilson, and co‐workers on page 4905. This technique is shown to create porous, elastomeric architectures with highly controlled mechanical properties, exhibiting markedly distinct load responses with directionally dependent behavior, including negative shear stiffness. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>